6
$\begingroup$

If $A$ and $B$ are $n\times n$ matrices of a field $F$, then show that $\text{trace}(AB)=\text{trace}(BA)$. Hence show that similar matrices have the same trace.

I've done the first part (proving that $AB$ and $BA$ have the same trace). I can show that here if you say so. But I'm stuck on the 'Hence show' part. Please give me some ideas.

$\endgroup$
  • 1
    $\begingroup$ Write up what it means for matrices to be similar and use what you have just shown. $\endgroup$ – Tobias Kildetoft Jul 1 '16 at 7:02
7
$\begingroup$

Hint: By very definition, two matrices $A,B$ are similar iff there exists an invertible matrix $S$ such that $A=SBS^{-1}$. Now apply the trace on both sides, and conclude using associativity of the matrix product.

$\endgroup$
  • 2
    $\begingroup$ Thanks a lot. $A=SBS^{-1} \implies \text{trace}(A) = \text{trace}\left((SB)(S^{-1})\right) = \text{trace}\left((S^{-1})(SB)\right) = \text{trace}\left((SS^{-1})B\right) = \text{trace}(B)$. Is this correct? $\endgroup$ – Aritra Das Jul 1 '16 at 7:05
  • 1
    $\begingroup$ That's it. Well done. $\endgroup$ – b00n heT Jul 1 '16 at 7:06
5
$\begingroup$

You can use the characteristic polynomials. If $A$ is similar to $B$, then their characteristic polynomials $f_A(x)$ and $f_B(x)$ are identical. Since $$ f_A(x)=x^n-tr(A)x^{n-1}+\ldots\pm\det(A)\\ $$ and $$ f_B(x)=x^n-tr(B)x^{n-1}+\ldots\pm\det(B) $$ it follows in particular that $tr(A)=tr(B)$.

$\endgroup$
1
$\begingroup$

It is very clear if you focus on the component. Let's say $$M = ABC$$then the trace in tensor notation is $$M^i_i = A^i_jB^j_kC^k_i$$ now you can see you can interchange them to form even permutation (so its $ABC,CAB, BCA$)without changing the invariant. Of course this works for any numbers of matrix multiplication as long as you got them in the right order
In so you push the $S^{-1}$ to the front and combine it with $S$, you will get identity and solve our problem

$\endgroup$
0
$\begingroup$

Suppose that $A$ is simular ti $B$, they there exist $C$ such that: $B=CAC^{-1}$. So: $tr(B)=tr(CAC^{-1})$, now let me call $X=CA$, and $Y=C^{-1}$, then $tr(B)=tr(XY)=tr(YX)=tr(C^{-1}CA)=tr(A)$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.